Estimating age and ethnic variation in the histological prevalence of prostate cancer to inform the impact of screening policies. - Leal, J; Hamdy, F; Wolstenholme, J (2014)
OBJECTIVES: To estimate histological prevalence of prostate cancer by age and ethnic group. METHODS: A literature review identified autopsy studies of men without clinical diagnosis of prostate cancer during their lifetime. A total of 25 studies fulfilled the inclusion criteria, and a Bayesian logistic meta-regression was carried out to examine the association between histological prevalence, age by decade and ethnic group (white, African American and Chinese/Japanese). RESULTS: Histological cancer was estimated to increase with age from 2% (95% confidence interval 1-3%) between 20-29 years-of-age to 69% (95% confidence interval 51-83%) by 90-99 years-of-age in the white ethnic group. The African American group was associated with the highest prevalence of cancer, albeit non-significantly (odds ratio 1.2, 95% confidence interval 0.9-1.5), whereas the Chinese/Japanese group was significantly associated with the lowest prevalence relative to the white group (odds ratio 0.6, 95% confidence interval 0.4-0.9). CONCLUSIONS: The present study provides an updated and improved analysis of the histological prevalence of prostate cancer. The results confirm ethnicity as a potential predictor of prevalence, but highlight the need for further research in the area. The findings are valuable for understanding the epidemiology and natural history of prostate cancer across ethnicities, and increasing the body of evidence aimed at estimating benefits and risks associated with prostate cancer screening programs.